Portraits and Gravestones: Documenting the Transnational Lives of Nineteenth-Century British-Métis Students - Millions, Erin (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2018)
The educational histories of mid-nineteenth century British-Métis students illuminate the transnational travels of British-Métis students and their roles in reifying and challenging British-imperial norms about race, class, and gender in the British Empire. In this paper, photographic and object-based artifacts are interwoven with family correspondence and other archival documents to explore the complexity of British-Métis children’s life stories and the extensive connections between elite British-Métis fur-trade families to kith and kin in North America and Britain. Studio portraits of British-Métis children and their gravesites represent both the best and the worst outcomes of elite educations for British-Métis children and youth. The studio portraits represent the norms of British middle-class respectability that elite British-Métis students learned at colonial and metropolitan schools as part of the imperial project. Gravestones and burial sites, on the other hand, reflect the possibilities and realities of death and trauma that were intertwined with fur-trade children’s boarding school education. By traveling to and living in Britain, British-Metis children challenged metropolitan understandings of the place and role of Indigenous peoples in the Empire and left their marks in Britain in their lives and their deaths.